ALIH AKSARA DAN ALIH BAHASA TEKS CERITA NABI ISA AS DALAM NASKAH CERITA NABI-NABI VERSI AZHARI ALKHALIDI RAHMATULLAH - Sari, Jeni Permata; Hasanuddin WS, Hasanuddin WS; Nasution, Bakhtaruddin (Jurnal Bahasa dan Sastra, 2013)
The purpose of this article to present change of the script and translation of story text of Isa in the Cerita Nabi-nabi manuscript Azhari Alkhalidi Rahmatullah version. Goal of this study in order textcan be readand understood bythe public andthe content ofthe text that containsthe values ​​andteachings ofreligionscan be knownby the public.The manuscriptwas written usingArabic-Malay script andMalay language. This study is a philology study and used descriptive method. The method that used was adjusted to the stage of study. On the stage of data collectoin used field research method. On the stage of data description used descriptive method. On the stage of change of the script used change of the script method. On the stage of translation used translation method. The result of this study is presented story text of Isa in theCerita Nabi-nabi manuscript Azhari Alkhalidi Rahmatullah version in Latin script and Indonesian language. The result of this study describe Isa life storystartsfrom the wombuntil hewas appointedby Godto heaven. In the textarearchaicwordsareretained.It aimstomaintain thepurity of thetext.